2006
DOI: 10.1016/s1569-9056(06)60389-8
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum a Toxin Intravesical Injections in the Treatment of Painful Bladder Syndrome: A Pilot Study

Abstract: e u r o p e a n u r o l o g y 4 9 ( 2 0 0 6 ) 7 0 4 -7 0 9 a v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . e u r o p e a n u r o l o g y . c o m Article info AbstractObjective: We evaluated the efficacy and tolerability of botulinum A toxin (BTX-A) intravesical injections in patients affected by painful bladder syndrome with increased urinary frequency, refractory to conventional treatment modalities. Methods: Twelve women and two men were prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 7 publications
1
38
1
1
Order By: Relevance
“…However, 10 patients experienced moderate to severe difficulties when attempting to empty their bladders. 55 Other studies, however, could not find any effect of BTX-A in IC/PBS. At the 2006 EAU meeting, Davies et al 56 presented results from a study of 13 patients with IC/PBS treated with BTX-A 100-300 U; 1 patient was reported cured, partial improvement was detected in 3 patients, and 9 patients worsened.…”
Section: Results With Rtx and Btx-a In Patients With Ic/pbsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, 10 patients experienced moderate to severe difficulties when attempting to empty their bladders. 55 Other studies, however, could not find any effect of BTX-A in IC/PBS. At the 2006 EAU meeting, Davies et al 56 presented results from a study of 13 patients with IC/PBS treated with BTX-A 100-300 U; 1 patient was reported cured, partial improvement was detected in 3 patients, and 9 patients worsened.…”
Section: Results With Rtx and Btx-a In Patients With Ic/pbsmentioning
confidence: 92%
“…Additionally, first desire to void and MCC increased by 58% and 57%, respectively. 54 In another pilot study, Giannantoni et al 55 concluded that intravesical BTX-A 200 U is effective in the short-term management of IC/PBS. Twelve of 14 patients (86%) reported subjective improvement at the 1-and 3-month follow-up point.…”
Section: Results With Rtx and Btx-a In Patients With Ic/pbsmentioning
confidence: 99%
“…Therefore, several small pilot studies were immediately carried out, none were placebo controlled, to explore the analgesic effects of onabotA in patients with chronic bladder pain as a result of BPS/IC. Unfortunately, conflicting results or weak and transient clinical improvements were reported . A prospective, randomized study enrolled 67 patients with refractory BPS/IC.…”
Section: Onabota Injection For Chronic Bladder Painmentioning
confidence: 99%
“…All of these studies involve patients who have failed at least one conventional treatment for BPS/ interstitial cystitis. Giannantoni et al [26] subsequently reported on the use of Ona-botulinumtoxinA in 14 patients, who had previously failed oral antidepressant, anticholinergic therapy or intravesical treatments of oral pentosan polysulphate. This study used doses of up to a maximum of 200 IU of both OnabotulinumtoxinA and AbobotulinumtoxinA, and utilized a trigone and floor of the bladder injection technique.…”
Section: Key Pointsmentioning
confidence: 99%